Effects of polypropylene twisted bundle fibers on the mechanical properties of high-strength oil palm shell lightweight concrete - Yew, M.K.; Mahmud, H.B.; Shafigh, P.; Ang, B.C.; Yew, M.C. (Springer Verlag (Germany), 2016)
In this study, the effects of a new type of non-metallic fiber (polypropylene twisted bundle (PPTB)) on the slump and mechanical properties of oil palm shell (OPS) concrete have been investigated. The results showed that increasing the volume fraction of PPTB fibers, it slightly decreases the workability and density of the concrete. It has found that the compressive strength of OPS concrete increases with increasing PPTB fiber volume fraction. The results revealed that the reinforcement of OPS concrete with steel and PPTB fibers reduces the strength loss of OPS concrete in poor curing environments. In addition, the fiber with low volume fraction (up to 0.25 %) is more efficient in improving the flexural strength of OPS concrete compared to its splitting tensile strength. The average modulus of elasticity (E value) is obtained to be 17.4 GPa for all mixes, which is higher than the values reported in previous studies and is within the range for normal weight concrete. The performance of the PPTB fibers is comparable to that for steel fibers at a volume fraction (Vf) of 0.5 %, which provides less dead load for lightweight concrete. The findings of this study showed that the PPTB fibers can be used as an alternative material to enhance the properties of OPS concrete. Hence, PPTB fibers are a promising alternative for lightweight concrete applications.